Model for an Inservice Science Teacher Training Program. - Bailey, Gerald D.; James, Robert K. (Science Education)
The article reports on the implementation of the Intermediate Service Curriculum Study (ISCS), a high school science program, by the U.S. National Science Foundation in the U.S. The goal of the project was to prepare the participants for assuming leadership roles in the implementation of ISCS in their home communities or regions. An underlying assumption for this was that classroom teachers, who are competent with respect to the innovation and possess the necessary leadership skills, can be effective leaders for the training of other teacher teachers in the implementation of new programs at the local level.